2018
DOI: 10.1111/jphp.12943
|View full text |Cite
|
Sign up to set email alerts
|

Impact of thymoquinone on cyclosporine A pharmacokinetics and toxicity in rodents

Abstract: A potential drug interaction between TQ and CsA, which may reduced its oral bioavailability. Independently TQ caused significant attenuation of CsA induced renal toxicity and diabetogenic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…One ml of cyclosporine A was mixed well with a 4 ml dextrose solution 5% to get a 10 mg/ml solution. This solution was used immediately (Alrashedi, Ali, Ali, & Khan, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…One ml of cyclosporine A was mixed well with a 4 ml dextrose solution 5% to get a 10 mg/ml solution. This solution was used immediately (Alrashedi, Ali, Ali, & Khan, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…A standard four-drug regimen, which includes isoniazid (H), rifampicin (R), and pyrazinamide (Z), usually with ethambutol (E) as a fourth drug during the first two months of treatment (intensive phase), followed by isoniazid and rifampicin for four additional months (continuation phase) [13,14]. However, surgery may be needed in the setting of complications such as obstruction, perforation, and fistulation or bleeding [15].…”
Section: Discussionmentioning
confidence: 99%
“…In the vancomycin group, the level of Cr, BUN and, malondialdehyde (MDA) were increased, TQ administration noticeably reversed these changes [18]. TQ usage in cyclosporine A (CsA) induced nephrotoxicity produced a small but nonsignificant decrease in serum Cr, and a significant decrease in Cystatin C. Histological assessments showed that co-administration of TQ with CsA prevented the major structural changes at both glomerular and tubular sides of rat's kidneys [19]. TQ supplemented with ifosfamide attenuated the severity of nephrotoxicity induced by ifosfamide.…”
Section: Role Of Tq In Drug-induced Nephrotoxicitymentioning
confidence: 99%
“…[18] TQ administration significantly ameliorated the increased levels of serum BUN, Cr and kidney tissue MDA in VCM group and the decreased activities of SOD and GSH-Px in kidney tissue Vancomycin(VCM)induced nephrotoxicity in rats [19] Administration of TQ significantly reversed the increased Cystatin C and alteration of kidney parenchyma Cyclosporine induced nephrotoxicty [22] TQ significantly reduced the BUN, Cr levels. The NO activity and tissue MDA levels were also reduced significantly.…”
Section: Nephrotoxicitymentioning
confidence: 99%